Pendidikan Islam dan Problematika Gender : Perspektif Barat dan Islam - Haikal Haikal (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This writing tries to present the dynamic of education and the gender problem. Women activities in the West and the East, especially Islam, are quite different. Usually the West is labeled as secular, while Islam is known as clumsy and backward, including in the matter of education and gender. Is this kind of perception valid and accountable compare to its realities ? Based upon intensive library research and intensive interviews, this study may highlight ideas in maintaining education by disregarding gender as there is not any gender problems in the Qur 'an and valid Hadith. This study presents the examples of dynamic gender based upon normative and empirical facts. As an early attempt, of course this study is full of weaknesses. Probably, some of the readers are interested in present their ideas whether they agree or disagree with this writing.